2000
DOI: 10.1034/j.1600-0447.2000.101006464.x
|View full text |Cite
|
Sign up to set email alerts
|

Service use and costs of people with dual diagnosis in South London

Abstract: Specific interventions for dual diagnosis patients should be introduced and assessed in terms of individual outcomes, service use and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…Diagnosis was predictive of higher psychiatric costs in six of the studies, with inconsistent findings for the other three studies. For example, McCrone et al (2000) found that a diagnosis of schizophrenia was a predictor of lower costs compared to the higher costs related to having a dual diagnosis, and concluded that patients with a dual diagnosis are more expensive to treat. Diagnosis was not always found to be very significant statistically in all of the studies ; for example, Knapp et al (1995) reported that diagnosis explained less than 1 % of the variation in costs, and concluded that diagnosis alone is of little assistance in predicting either service requirements or costs.…”
Section: Factors Related To Higher Of Lower Costsmentioning
confidence: 99%
“…Diagnosis was predictive of higher psychiatric costs in six of the studies, with inconsistent findings for the other three studies. For example, McCrone et al (2000) found that a diagnosis of schizophrenia was a predictor of lower costs compared to the higher costs related to having a dual diagnosis, and concluded that patients with a dual diagnosis are more expensive to treat. Diagnosis was not always found to be very significant statistically in all of the studies ; for example, Knapp et al (1995) reported that diagnosis explained less than 1 % of the variation in costs, and concluded that diagnosis alone is of little assistance in predicting either service requirements or costs.…”
Section: Factors Related To Higher Of Lower Costsmentioning
confidence: 99%
“…In south London over a decade ago researchers found over a six month period the cost per service user was £1,469 more for those with schizophrenia and substance misuse (McCrone et al 2000). Many of this group are known to the criminal justice system as well.…”
Section: Drug Use and Psychosismentioning
confidence: 99%
“…A number of epidemiological studies conducted mainly in the United States indicate that this comorbidity is very high, greater in subjects under treatment, and that the concomitant presence of several disorders has major clinical, evolutionary, and therapeutic implications (Compton, Thomas, Stinson, & Grant, 2007;Swendsen et al, 2010).Dual disorders have been associated with an increase in the number of psychiatric admissions (Hunt et al, 2002); violence (Soyka, 2000); suicidal behavior (Appleby et al, 1999), an increase in health expenditure (McCrone et al, 2000), greater medical comorbidity (Dickey, Normand, Weiss, Drake, & Azeni, 2002), poor adherence to treatment (Kamali et al, 2001), and limited results of the latter in both pathologies (Carey et al, 1991).…”
Section: Introductionmentioning
confidence: 99%